Avaliação de desempenho de métodos para estimativa da evapotranspiração de referência (eto) - Freitas, Isaac Alves da Silva (Universidade Federal Rural do Semi-Árido, 2019)
The municipality of Mossoró stands out in the regional agricultural scenario, being considered, great productive potential in the fruticulture of the Northeast region. The municipality has a constant water deficit, it is necessary the development of irrigated agriculture and the efficient use of water, for this it is necessary the knowledge of the reference evapotranspiration (ETo), for the calculation of the water needs of the crops. Therefore, the objective of this work was to evaluate several ETo estimation methods, in order to make feasible a reliable method that involves a smaller amount of input variables than the FAO standard method, for the climatic conditions of Mossoró. The methodology used tested different methods of estimation of the reference evapotranspiration, comparing them with the standard Penman-Monteith-FAO method 56, later the linear regression of the data was, verified, verifying the existence or not of significance between the values found, indicating the best and worst methods compared to the Penman-Monteith-FAO method 56. According to the statistical indices used, the best performance was, obtained by the Penman Original (PO) method, while the worst method was due to the methodology proposed by Thornthwaite and Camargo (TTC). The original Penman method (PO) obtained values of (d = 1.0, c = 0.91 and EPE = 0.54mm / day), while the TTC obtained values of (d = 0.99, c = -0,05 and EPE = 4,19mm / day). When the viability of the methods were tested, all of them were viable, according to the t test, with the exception of TTC, which showed very low reliability, being recommended to be excluded from use without prior calibration for our conditions.
Keywords: Manejo da irrigação; Análise de sensibilidade; Penman-Monteith; Curva de sensibilidade.; Irrigation management; Sensitivity analysis; Penman-Monteith; Sensitivity curve; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO